The Implementation Of Comprehensive Montessori Method For The Teaching Of English Language At Singapore Piaget Academy International School Solo Baru - Handayani, Sri, Prof. Dr. Endang Fauziati, M. Hum, Dra. Malikatul Laila, M. Hum (2014)
The objective of the study is creating children to be Bilingual in English language as the second language, and to create outstanding young children who are, independent, discipline, responsible, and creative by providing a type of learning system called Montessori. It‟s a type of learning approach that provides attractive set of educational materials and books, creative teachers and supporting environment. Children learn English language actively at school, and children learn English language from: Listening, Speaking, Reading and Writing lessons. The research Methodology included setting and time of the research started from September to March 2013 in Play Group II Class at Singapore Piaget Academy International Elementary School Solo Baru. There are nine research questions that the writer has set in her study. The type of the research is descriptive qualitative research. The data of the study consists of the materials of the English lesson, the result of interview from teachers, students and parents. Besides that the writer also documented some events and learning activities. The study was classified into some steps; observation, get the data and find the results. There are some research questions that the writer has prepared. Those questions are included; what are syllabus model of Montessori learning?. What are the general and specific learning objectives of the school?. What are the classroom techniques of the school ?. What are the instruction materials used by children ?. What are the teacher‟s and student‟s role ?. What are the media used ?. What are the supporting components of Montessori Lesson ?. What are the evaluation of the teaching learning ? And also what are the procedure of teaching learning in Singapore Piaget Academy International School solo Baru.? The writer concluded that children have innate desire to learn and explore, with parent, peers and environment support they can achieve good quality of learning. The quality of learning itself is not the result but the processes that occur everyday.